A diversidade beta como ferramenta para determinação de riachos prioritários para ações de manejo e gestão. - Barboza, Luís Gabriel Antão (2014)
The beta diversity has become indispensable to the understanding of ecosystem functioning and to determining priority areas for biodiversity conservation. Nevertheless, patterns of beta diversity of invertebrates are little known in aquatic ecosystems of the tropical region. Thus, using data from small order streams located in southern Brazil, we tested the hypothesis that increased environmental heterogeneity raises the beta diversity of Chironomidae in streams with more severe human impacts. The streams were grouped into rural and urban, according to the percentage of urbanization of the watershed of each. The results support the hypothesis and demonstrated that the physical and chemical characteristics of the water are not different only distinct between types of streams, but also more heterogeneous in urban streams. Therefore, the composition of Chironomidae differs between rural and urban streams and responds to environmental heterogeneity. For this reason, the beta diversity was affected, being higher in urban streams. Our results suggest that beta diversity can be an effective tool not only to proposing guidelines and determining priority areas for conservation, but also to indicate potentially degraded and priority sites for water management.